Exploring genetic variability, diversity and trait associations in sunnhemp (Crotolaria juncea L.) accessions for yield improvement - Pushpa, R; Shanmugam, A; Arulmozhi, R; Sassikumar, D; Suresh, R; Subrahmaniyan, K (Plant Science Today, 2025)
Sunnhemp (Crotolaria juncea L.) is an important fibre crop known for its rapid growth and ability to improve soil fertility, making it a vital component of sustainable agriculture. However, to enhance its productivity and meet the increasing demand for high-quality fibre, it is crucial to identify and utilize genetically diverse genotypes with superior yield traits. The present study was conducted at the Tamil Nadu Rice Research Institute, Aduthurai, Tamil Nadu, during the Kharif seasons of 2021 and 2022 to assess genetic variability and character association for yield and its component traits among 67 sunnhemp genotypes. Multivariate analyses, including principal component analysis (PCA) and cluster analysis, were conducted using R software to dissect the phenotypic diversity among the genotypes. The results revealed substantial genetic variability for yield and its associated traits, indicating a promising potential for genetic improvement. Genotypes ADSH 1750, ADSH 1701, ADSH 1736, ADSH 1715, and ADSH 1742 exhibited superior performance in key yield-related traits, making them valuable candidates for future breeding programs focused on developing high-yielding, high-fibre varieties. Cluster analysis delineated four distinct clusters, with Clusters I and IV showing significant divergence and highlighting the presence of unique genetic material. Key plant production traits such as plant height, leaf breadth, basal stem diameter, yield, and number of leaves were the primary contributors to the first two principal components. These findings suggest that direct selection based on these traits could effectively improve biomass yield in future sunnhemp breeding efforts, contributing to the advancement of sustainable fibre crop production.